2010
DOI: 10.1016/j.jweia.2009.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Real-time performance monitoring of tuned mass damper system for a 183m reinforced concrete chimney

Abstract: A 183m reinforced concrete chimney for a coal-fired power station was instrumented in the latter part of its life during the construction of a replacement chimney. Because of concerns about large-amplitude response induced by interference effects from the new chimney in the prevailing upwind direction, a response monitoring system was installed, quickly followed by a tuned mass damper (TMD) system. As well as providing live display of the chimney response, the monitoring system was also used to check the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 12 publications
(15 reference statements)
0
32
0
1
Order By: Relevance
“…Not many examples of "twin chimneys" can be found in literature, nevertheless a quite similar study confirmed the mitigation of the wind-induced vibrations reached by installing a TMD device similar to those installed at Rovinari Power Station, [11]. Figure 2 shows the TMD after its installation one chimney.…”
Section: Introductionmentioning
confidence: 55%
“…Not many examples of "twin chimneys" can be found in literature, nevertheless a quite similar study confirmed the mitigation of the wind-induced vibrations reached by installing a TMD device similar to those installed at Rovinari Power Station, [11]. Figure 2 shows the TMD after its installation one chimney.…”
Section: Introductionmentioning
confidence: 55%
“…Moreover the monitoring system allowed observing changes on the modes due to structural effects from TMD, in addition to expected changes due to temperature-dependent changes in concrete modulus. Other influences on the modes are the wind and its directional effects due to the construction of the new chimney close to the old one [10]. Environmental effects are always present on outdoor civil structures.…”
Section: Monitoring System Design and Adquisition Signal Processingmentioning
confidence: 99%
“…Noting the exorbitant rise in the project cost, it is of interest to analyze reduction in the response and the consequent shear force by using some alternative approaches. Recently, Brownjohn et al [9] had shown the effectiveness of tuned mass damper (TMD) to control the responses of an old chimney. They installed a TMD on a 183 m high old chimney to improve the damping of the chimney.…”
Section: Introductionmentioning
confidence: 99%